2019
DOI: 10.1182/blood-2018-06-858159
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD117 antibody depletes normal and myelodysplastic syndrome human hematopoietic stem cells in xenografted mice

Abstract: The myelodysplastic syndromes (MDS) represent a group of clonal disorders that result in ineffective hematopoiesis and are associated with an increased risk of transformation into acute leukemia. MDS arises from hematopoietic stem cells (HSCs); therefore, successful elimination of MDS HSCs is an important part of any curative therapy. However, current treatment options, including allogeneic hematopoietic cell transplantation (HCT), often fail to ablate disease-initiating MDS HSCs, and thus have low curative po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 40 publications
1
42
0
1
Order By: Relevance
“…Indeed, recognition of the adverse impact of pre-transplant conditioning has led to increasing interest in the use of reduced intensity conditioning or alternative protocols for clinical HSCT. For example, it has recently been shown that depleting endogenous murine HSPCs by administering an antibody-bead conjugate against CD117, allows for the survival and differentiation of human HSPCs in non-conditioned NSG mice (35,36). With this approach now entering phase-I clinical trials, murine models that provide an HSPC-deficient host environment will likely become increasingly useful tools for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recognition of the adverse impact of pre-transplant conditioning has led to increasing interest in the use of reduced intensity conditioning or alternative protocols for clinical HSCT. For example, it has recently been shown that depleting endogenous murine HSPCs by administering an antibody-bead conjugate against CD117, allows for the survival and differentiation of human HSPCs in non-conditioned NSG mice (35,36). With this approach now entering phase-I clinical trials, murine models that provide an HSPC-deficient host environment will likely become increasingly useful tools for further research.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44] Finally, our group recently showed that an anti-CD117 (c-KIT) antibody can deplete MDS hematopoietic stem cells and restore normal donor hematopoiesis in xenografted mice. 45 Combining this c-KIT antibody with TLI-ATG conditioning for patients with MDS and AML may deplete stem cell niches, thereby improving donor cell engraftment and chimerism.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in antibody-based therapeutics have presented the possibility of targeted conditioning agents. 13,48 Clinical trials have begun with unconjugated antibodies as conditioning agents (NCT02963064). The potent effect demonstrated by DCR-2-PBD against healthy HSPCs suggests that therapeutic derivatives targeting CD300f may be incorporated into conditioning for nonmalignant disorders of erythropoiesis or immunodeficiency either as part of an allo-HSCT or a gene-modified autologous HSCT.…”
Section: Discussionmentioning
confidence: 99%